O que fazer para sobreviver politicamente?: padrões de carreira dos deputados estaduais no Brasil - Filipe Souza Corrêa (2016)
This thesis is about the political careers of state deputies in Brazil, and its goal is to analyze the effects of the state deputies spatial voting patterns on political career survival strategies. The objective is to answer how much the way the subjects relate to their electoral bases (electoral connections),shapes identifiable political career patterns among the elective offices available in the opportunity structure (defined by the costs and benefits of each choice) in Brazil. The data source used was the Superior Electoral Courts Electoral Data Repository. The career pattern analysis of the state deputies elected in 2010 from a predominant career ambition perspective (if national progressive, state progressive, static, pseudo-static, localprogressive, or discrete), defined by the combination of the state deputies origin and destination trajectories throughout five elections, indicated a certain equilibrium towards a manifest preference for static ambition. Moreover, it was identified that spatial voting patterns (constructed from a combination of concentration and dominance indicators), have some relation to deputies career patterns, corroborating the hypothesis that these spatial patterns shape the preferences for positions available in the opportunity structure. However, according to the Theory of Political Ambition, it is not only the benefits that situate the decision on which office to run for, but also the risks involved in that decision. Based on that hypothesis, the empirical analysis of the relationship between the individual attributes of the candidates votes and the degree of uncertainty inherent to the competition for offices showed that, in some cases, the risk calculations make necessary an adjustment on the manifest political ambition, adapting the short-term ambition to a more realistic scenario according to the deputys electoral extraction characteristics.